Implementation of the project to strengthen the profile of pancasila students in primary schools - Rahma, Nadia; Mustika, Dea (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This research aims to analyze the implementation of the Pancasila Student Profile Strengthening Project Program (P5) at SDN 006 Air Molek Satu. A qualitative approach is used in research using observation, interviews and documentation as data collection techniques. The data that was collected was analyzed through a series of stages, including data reduction, data presentation, and verification, with the aim of producing conclusions based on the findings during the research. The results of the research show that the implementation of the Project for Strengthening the Profile of Pancasila Students at SDN 006 Air Molek Satu includes several activities, namely starting from the formation of a team of facilitators. Where the facilitator is formed by the principal as the person in charge while the class teacher becomes the facilitator between phases, then identifying school readiness by preparing modules. and expenditure tools, then selecting character dimensions, determining themes, time planning, carrying out assessments. The assessment is carried out through assessing the development of the dimensions of the Pancasila student profile and assessing product results. The results of the evaluation and project carried out show that the development of the dimensions of the Pancasila student profile in class I, II, IV, V in the dimensions of Faith and Devotion to God Almighty and having noble morals has reached the level of development according to expectations, in the dimension of mutual cooperation on average. reached a highly developed level, and in the creative dimension the average was at a developed level according to expectations. However, in this implementation, there were also activities that were not optimal at SDN 006 Air Molek Satu, namely in the module preparation section. In this activity the teacher has not been able to develop modules in a sustainable manner, the modules used are still taken and adapted from the internet and the PMM platform, this is due to the teacher's lack of understanding in developing project modules. This research is important to carry out because in the era of the independent curriculum there is more emphasis on P5 activities as an effort to instill the dimensions of the Pancasila student profile in students so that it can have a positive impact on the world of education.